Microplastic accumulation in snake-eyed lizard (Ophisops elegans Menetries, 1832) after long-term monitoring: habitats matter, not years - Cantekin Dursun; Kamil Candan; Kaan Karaoğlu; Çetin Ilgaz; Yusuf Kumlutaş; Elif Yıldırım Caynak; Serkan Gül (Environmental Sciences Europe)
Abstract Microplastics (MPs) have become pervasive environmental pollutants with significant impacts on ecosystems, particularly aquatic environments. As these particles infiltrate various habitats, they are ingested by a wide range of organisms, from plankton to large marine mammals. The ingestion of MPs disrupts the food web, causing physical and chemical harm to animals at multiple trophic levels. Here, we studied the accumulation of MPs in the gastrointestinal tracts (GITs) of a terrestrial lizard species after long-term monitoring using museum specimens in the collection of the Fauna and Flora Research and Application Center at Dokuz Eylül University from decades ago. These museum samples were from 1986 to 2013, but not consecutive years. GITs from 300 individuals were analyzed and MPs were detected in the GITs of only 25 individuals. In 25 individuals, the most dominant form of microplastic was fiber. The highest number of MPs was detected in 2001, followed by 1995. It is thought that this accumulation is caused by human activities in the lizard's environment and that it enters the food web indirectly because it lives in areas with high human interaction. Overall, this study shows that MPs have been present in the past, entering the food web of terrestrial species, and that MPs can inherently transfer to other living things. It is understood that MPs will pose significant threats to biodiversity and ecosystem health as they are transferred through the food chain. Graphical Abstract